Radial artery pseudoaneurysm as a rare very late complication of transradial cardiac catheterization - Nykl, Radomir; Precek, Jan; Spacek, Milos; Sluka, Martin; Hudec, Stepan; Heinc, Petr; Taborsky, Milos (Biomedical papers, 2021)
Aims. Here, we report a case of very late (70+ days) development of pseudoaneurysm on the site of sheath insertion in a 60- year old woman.Methods. The patient underwent cardiac catheterization using transradial approach.Results. Despite the transradial approach, which is generally considered as a suitable prevention of this problem, and despite absence of any periprocedural complications, the patient developed a pseudoaneurysm after more than 70 days from the procedure.Conclusions. In some cases, a pseudoaneurysm may develop extremely late after cardiac catheterization. Such an extremely late development of pseudoaneurysm has not been described in literature so far.
Keywords: pseudoaneurysm; transradial approach; cardiac catheterization